NCMP-06. VENOUS THROMBOEMBOLISM INCIDENCE AND THE IMPACT OF PRE-DISEASED ANTICOAGULATION THERAPY IN GLIOBLASTOMA PATIENTS. (14th November 2022) - Sloan, Anthony; Elder, Theresa; Desai, Ansh; Wu, Anna; Choi, Serah; Sloan, Andrew
Abstract: Glioblastoma (GBM) patients have a 24-30% risk of developing venous thromboembolism (VTE), including deep vein thrombosis or pulmonary embolism, over the course of their diagnosis. However, very little data exists regarding the impact of VTE on survival in GBM patients, with or without anticoagulation. This study aimed to investigate 1) the demographic factors associated with VTE incidence in GBM patients, 2) any correlation between VTE incidence and length of survival and, and 3) the impact of pre-diagnosis antiplatelet/anticoagulation therapy on VTE development and survival. A total of 150 GBM patients treated at University Hospital Seidman Cancer Center were included and retrospectively analyzed. Information was collected regarding history of aspirin, clopidogrel, DOAC, heparin, and/or warfarin use. The diagnosis of VTE both prior to GBM diagnosis and at various time points following diagnosis was determined followed by calculating overall survival and progression free survival (PFS). Of the 150 GBM patients, 53 (35.3%) developed a VTE overall. VTE incidence correlated with a lower KPS at presentation (r = -.225, p =.027) and a decrease in overall survival among GBM patients (r = -.191, p =.041). Antiplatelet/anticoagulation therapy prior to GBM diagnosis correlated with decreased VTE formation overall, as well as longer PFS among non-VTE patients (r =.261, p = .026) but not among patients who later developed VTE (r = .165, p = .302). Our findings demonstrate that patients with lower KPS are at a higher risk for developing VTE. Among GBM patients who did not develop VTEs, those on antiplatelet/anticoagulation therapy prior to diagnosis had longer PFS compared to those who were not on anticoagulants. These preliminary studies highlight the need for better VTE prophylaxis and therapy among GBM patients. These results further suggest the potential benefit of anticoagulation therapy in GBM patients irrespective of VTE formation.